Ontogenia craniana comparada de Arctocephalus australis, Callorhinus ursinus e Otaria byronia (Otariidae: Pinnipedia) - Sanfelice, Daniela (2003)
The search for mechanisms that can generate major morphological changes has led to the study of ontogeny, in part because some kinds of modifications of ontogenies seem an excelent way to generate major phenotypic change. We focus here on Arctocephlaus australis, Callorhinus ursinus and Otaria byronia with the aim of contributing to the understanding of the origin, structure and temporal patterns of otarid morphological diversity. The pattern of change in shape during postnatal development in otarid skull was studied and described by geometric and traditional morphometrics. Our aims are: to compare the skull ontogeny of the species invocated in identifying and in describing shape alterations in the skull; to evaluate and to describe comparatively the sexual dimorphism and disparity during the ontogeny; to study the covariance between size and shape in relationship with age-groups; to investigate the changes in the ontogeny and their relationships with the evolution of the Otariidae Family; to analyze the conservation of ontogenetic trajectories over time, between sexes and among species; to characterize growth trajectories and to compare them among taxa with respect to isometry; to describe the parameters of growth and development of the focused species and to compare the two different approaches employed. Using traditional morphometrics, the allometry vectors for all species were significantly different from isometry. Dimorphism in the allometric vector is observed only in O. byonia and the difference between males and females of the fur seals are related with adult body size. The comparisons species/sex groups revealed similar vectors (any significant shape disassociation are verified in the inter-specific analyzes), suggesting lower plasticity of the ontogenies. Using geometrical methods, the dimorphism is more conspicuous in adult shapes but this is not true for the level of disparity between sexes of O. byronia. Although that dimorphism is linked with size this is not only a question of scaling or allometry (which is present in the morphogenesis of all species, especially in O. byronia). Additionally, the slopes of changes in shape related with size increase are different in A. australis and O. byronia, but are equal in C. ursinus, which is the smaller species. We suggest post-displacement as one of the factors that could have acted in the origin of the sexual dimorphism in the skull of C. ursinus. Heterochrony, perhaps is present in the roots of the modifications suffered by the ontogeny of A. australis and O. byronia too, considering the differences in the rates of development between the sexes of both species (and overall in O. byronia), but surely repatterning allometric is involved too in these cases. We verified that ontogenies can not be summarized by a single linear vector in any analyzed group, where C. ursinus ontogeny is the more linear and O. byronia the more multi-dimensional species among the 3 that we had examined. Shape changes in the otarids studied here are more related with size than with age and any of the species share a common growth allometry or a common ontogenetic trajectory/pattern. In the same way, shapes at onset or offset are not the same in any case. When the three species are pooled together, initial shapes are always very different among the species and the distances between shapes increase with time almost independently from size. On the other hand, when the complete samples are considered, all the ontogenetic trajectories are significantly different in the directions of the allometric vectors during ontogeny. Ontogenetic trajectories differ significantly among almost all the pairs compared, except for the trajectories of A. australis and C. ursinus males. They are no more different than expected by chance considering the range of angles within each sample. A similar pattern is found when the subadults are compared between pairs of species and when we compare adult males of A. australis with adult males of O. byronia. The juveniles are no more different than expected by chance (correlation between ontogenies in that phase is equal to one), excepti between C. ursinus and O. byronia. The ontogenetic trajectory of C. ursinus is the shorter and of O. byronia is the longer being almost three times longer than the former. A. australis has an intermediary length of ontogenetic trajectory. For the sample comprising all three species disparity increase significantly over ontogeny since the disparity of the adults is near the two times of the disparity between juveniles. For any ontogenetic stage, O. byronia is the species that contributes for the disparity of the all group, followed by C. ursinus. When we consider the three species together, the pattern of disparity do not change a lot during ontogeny. Ontogenies examined herein are clearly not constrained and perhaps the differences in patterns have additive effects in the differentiation of the ontogenies. Whether ontogenetic trajectories are linear or curve could be a function of developmental timing or more specifically it could depend on the age at which allometries stabilize in post-natal ontogenies. Otherwise, the amount of differences between species in the ontogenies is in agreement with the phylogenetic relationships. Finally, we addressed basically the following questions: Is onset time the same in the species? Is offset time the same in these species? Does growth rate differ between the species. The answer to those questions could be summarized by the conclusion. but we conclude that the changes in otarids skull ontogenies had occurred in spatial and temporal terms.